The Impact of The Human Development Index and Unemployment on Economic Growth in West Papua Province - Agustina Ester Antoh; Stephanny Inagama Timisela; Hirim Monalisa Tambunan; Luciana Imanuella Pallo (AIBPM Publisher, 2024)
West Papua Province is one of the regions in Indonesia with relatively low economic growth. According to data from the Central Statistics Agency (BPS), the province recorded an economic growth rate of 3.73% in the third quarter of 2023. Several factors contribute to this condition, including the Human Development Index (HDI) and the unemployment rate, which are often associated with regional economic performance. This study aims to analyze the effect of HDI and unemployment on the economic growth of West Papua Province during the period 2011–2023. The research method used is multiple linear regression analysis. The t-test is used to examine the partial effect of each variable, the F-test is used for simultaneous testing, and the coefficient of determination (R²) is used to assess the model's explanatory power. The results show that: (1) the Human Development Index (HDI) has a significant positive effect on economic growth; (2) the unemployment rate also significantly affects economic growth; and (3) both variables simultaneously have a significant influence on economic growth in West Papua Province. These findings indicate that improvements in human development and employment conditions are essential to stimulate economic growth in the region.